Developing an Employer Branding Model based on the Expectations of Talented Employees - Shirin Mazraeh (University of Tehran, 2021)
Objective Organizations strive to propose a clear and unique intra- and inter-organizational image to show their advantages over other employers. This is conceptualized as the employer brand, which includes the combination of the efforts that an organization makes not only to retain their talented workforce, but also to be the first choice of job seekers. It is noteworthy that the company must be one of the best companies in order to attract the best employees. Successful employer branding requires addressing the factors that are important for the talented workforce. Therefore, it is essential to identify positive points in the eyes of talented workers and consider a statistical population of talented workers regardless of the type of organization, which highlights the need to provide a comprehensive and new model in this study. It is thus necessary to conduct this research because Tehran labor market includes a wide range of organizations. Therefore, talented employees have more choices and it is easy to find different types of characteristics that affect their job choices in this labor market and the appropriate statistical community for the present study. Hence, this study seeks to illustrate what is important for a talented workforce about the ideal employer and to provide managers with solutions to create an effective employer brand. Methodology This survey research is applied in terms of purpose and has been conducted using in-depth and semi-structured interviews and a questionnaire survey. At first, the grounded theory was applied to design the employer branding model with a qualitative approach, and then the model was assessed using a quantitative approach. Data were collected using a semi-structured interview with 25 graduates of different postgraduate and doctoral programs, who have been employed in the labor market of Tehran during the research. The desinged model led to the distribution and collection of 437 questionnaires. The analysis of the interview data was performed using open, axial, and selective coding based on Strauss and Corbin’s model using Nvivo 10 software. The quantitative part of modeling was assessed using structural equations via SPSS 25 and AMOS 24 software.   Findings The findings of the qualitative part led to the development of the employer branding model based on the perspectives of talented employees in the Tehran labor market, including causal conditions: what the employer promises to the knowledge employees is based on their expectations of the organization, manager, and the job. These expectations are based on Maslow's hierarchy of occupational needs. Phenomenon-orientation: the main category in employer branding is identifying the potential clashes of the individuals with the organization and dealing with their experiences so that the employer brand can be managed in the minds of people. Contextual conditions: if an organization has a lot of power resources i.e., organizational capabilities and competencies including organizational empowerment, products, and engagement in the international market, it has prepared the requirements for employer branding. Besides, it enjoys the cooperation and support of all employer branding trustees, and its human resource management operates at an appropriate level of maturity leading to a better platform for employer branding. Intervening conditions: the employer's brand experience and the strategies that individuals pursue are influenced by the type of dominant characteristics of job candidates, the conditions under which the brand content is marketed, and how the employer and employees address the employer's branding challenges. Strategies: these are introduced at both the employer and employees’ levels. Outcomes: the consequences of branding that result from the adoption of different strategies by the employer and the workforce are classified into different areas of recruitment and retention, employees, organizational performance, customer and market, brand awareness, human resources, business brand, and secondary outcomes. Conclusion The results of data analysis showed that the mutual expectations of the individuals, job, and organization can lead to the creation of the employer brand experience. Along with the contextual conditions (organizational power resources, executive requirements of employer branding, employer branding trustees, and human resource management subsystems) and intervening conditions (job candidate image, employer content marketing, and employer branding challenges), this experience leads to employer strategies in brand promises and employees’ strategies so as to decide whether to stay or leave the organization. It will ultimately results in employer branding consequences.